Keeping a Household Inventory and Protecting Valuable Records - Regina Fegan; Michael T. Olexa (EDIS)
A disaster strikes. Your home and possessions are destroyed. Will you be able to pick up the pieces? You will, if you: keep an up-to-date household inventory and keep this and other valuable documents in a secure location. This publication provides details about these two tasks. This document, IFAS publication DH0207, was published June 1998, revised May 2003. It is part of The Disaster Handbook, a component of the Comprehensive Disaster Preparedness and Recovery Education Module.